Answer:
39
Step-by-step explanation:
the answer is 39 because you do 65/5 which gives you 13 and then you multiply 13 by 3. pls mark as brainliest
Answer:
The first equation should be multiplied by 9 and the second equation by −4
Step-by-step explanation:
Given the simultaneous equation
First Equation: 5x − 4y = 28
Second equation: 3x - 9y = 30
In order to eliminate y, we must make the coefficient of x in both expression to be equal.
To do that the first equation should be multiplied by 9 (negative value of the coefficient of y in equation 2)and the second equation by -4( (coefficient of y in equation 1)
Answer:
у = x² + 7x - 30
Step-by-step explanation:
x₁ = 3 and x₂ = -10
Use the formula (x - x₁)(x - x₂) = 0
(x - 3)(x - (-10)) = 0
(x - 3)(x + 10) = 0
x² + 10x - 3x - 30 = 0
x² + 7x - 30 = 0